Investigating preservice chemistry teachers' eye movements while working with macroscopic, symbolic and submicroscopic level of representations for chemical equilibrium - Korkmaz Yavuz, Şule. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
The aim of current study is to analyze the eye movements of preservice chem istry teachers according to their experience in multiple representations. In this respect a CEV, which visualizes the chemical equilibrium at three representational levels simul taneously, was demonstrated and then a screen test was applied about it. Preservice chemistry teachers were divided into two groups: the ﬁrst group (called PCT1, N=18) got trained about multiple representations before the study, whereas the other group (called PCT0, N=22) did not. In order to achieve the aim of this study mixed method design was conducted. The mean scores of CEV Pretest and Posttest were analyzed with Wilcoxon Signed-Rank Test and it revealed that CEV is eﬀective on improving the preservice chemistry teachers? ability of representing the chemical equilibrium at the macroscopic and submicroscopic level (p < .001). Chi-Square Test for Indepen dence was used to investigate the relation between the mostly referred representation level on the screen and the experience in multiple representations and no statistically signiﬁcance (p = .534) was found. Additionally, Mann Whitney U Test was applied to examine the correlation between the preservice chemistry teachers’ experience in multiple representations and the kind and number of saccades on the screen. The re sult of analysis indicated that PCT1 made more transitions between the symbolic and submicroscopic representations (p < .05). Lastly, Chi-Square Test for Independence demonstrated that the preservice chemistry teachers’ saccades among the representa tional levels and their verbal explanations were aligned (p > .05).
Keywords: Chemistry teachers.; Chemical equilibrium.